Comparative law - Kischel, Uwe; Hammel, Andrew, 1968- (Oxford, United Kingdom : Oxford University Press, 2019)
This treatise offers in-depth coverage of comparative law, carefully structured and clearly explained by a leading expert. It is an invaluable resource for students seeking a critical introduction to the field, as well as scholars and practitioners, for whom it offers new insights, structures, and approaches.
Part I. General Aspects of Comparative Law -- 1. Introduction: What Is Comparative Law? -- 2. Aims of Comparative Law -- 3. The Comparative Method -- 4. Legal Families, Legal Culture, and Context -- Part II. The Contexts of Legal Systems -- 5. The Context of Common Law -- 6. The Basic Context of Civil Law -- 7. Variety of the Civil Law Context -- 8. The Context of African Law -- 9. Contexts in Asia -- 10. The Context of Islamic Law -- 11. Contexts of Transnational Law.
Includes bibliographical references and index.
Translated from the German.
Keywords: Comparative law; Law -- Methodology; Law -- Philosophy